Enhancement of terahertz photonic crystal cavities patch antenna performances using resized ground plane and slotted techniques / Nur Alinawati Baharom - Baharom, Nur Alinawati (2017)
This paper presents a simulation and analysis of a rectangular microstrip patch with photonic crystal cavities (PCC) (PTFE) as a substrate material at 0.6 Terahertz using electromagnetic computer simulation tools. The substrate utilize a 2-D photonic crystal type.